Loneliness, Social Isolation and Their Difference: A Cross-Diagnostic Study in Persistent Depressive Disorder and Borderline Personality Disorder - Nenov-Matt, Tabea; Barton, Barbara B.; Dewald-Kaufmann, Julia; Goerigk, Stephan; Rek, Stephanie; Zentz, Katharina; Musil, Richard; Jobst, Andrea; Padberg, Frank; Reinhard, Matthias A. (Frontiers in Psychiatry, 2020)
Background: Interpersonal difficulties are a key feature of persistent depressive disorder (PDD) and borderline personality disorder (BDP). Caught in a vicious circle of dysfunctional interpersonal transaction, PDD and BPD patients are at great risk of experiencing prolonged loneliness. Loneliness, in turn, has been associated with the development of mental disorders and chronic illness trajectories. Besides, several factors may contribute to the experience of loneliness across the lifespan, such as social network characteristics, a history of childhood maltreatment (CM), and cognitive-affective biases such as rejection sensitivity (RS). This cross-diagnostic study approached the topic of perceived loneliness by comparing PDD and BDP patients with healthy controls (HC) in its interplay with symptom burden, social network characteristics, RS as well as CM. Method: Thirty-four PDD patients (DSM-5; 15 female, Mage=38.2, SD=12.3), 36 BPD patients (DSM-5; 19 female, Mage=28.8, SD=9.2), and 70 age- and gender-matched HC were assessed cross-sectionally using the following self-report measures: UCLA Loneliness Scale, Social Network Index (SNI; size, diversity, and embeddedness), Beck Depression Inventory (BDI-II), Borderline Symptom List (BSL-23), Childhood Trauma Questionnaire (CTQ), and Rejection Sensitivity Questionnaire (RSQ). Results: Both patient groups reported significantly higher levels of perceived loneliness, symptom severity and smaller social network characteristics compared to HC. Loneliness was significantly correlated with severity of self-reported clinical symptoms in PDD and at trend level in BPD. Besides, loneliness tended to be related to social network characteristics for all groups except PDD patients. Both PDD and BPD patients showed higher RS as well as CTQ scores than HC. A history of emotional abuse and emotional neglect was associated with loneliness, and this association was mediated by RS as demonstrated by an exploratory mediation analysis. Discussion: Loneliness is highly prevalent in PDD and BPD patients and contributes to the overall symptom burden. Interestingly, loneliness showed an association with prior experiences of CM as well as current RS. We therefore propose a comprehensive model on how intra- und interpersonal aspects may interplay in the dynamics of loneliness in light of CM. Finally, this model may have further implications for psychotherapeutic interventions.